Doing-together with words: the sequential unfolding of a moment of meeting in a psychoanalytic therapy session - Herrera, Marcos; Ugarte, Andrea; Vásquez-Torres, Gabriela; Durand, Kene M.; Sánchez, Miguel (Frontiers in Psychology, 2023)
This paper draws on the methods and findings of Conversation Analysis (CA), particularly Peräkylä's (2019) sequential model of psychotherapy interaction, to examine how a moment of meeting, which resolves a challenge to the intersubjective relationship posed by a now moment (Stern 2004), comes about interactionally. We present a single-case analysis of an episode from the final session of a brief psychoanalytic therapy in Peru (in Spanish) with a female client victim of domestic violence. Our analysis reveals how a transformation of relation -the transitory emergence of a new form of relatedness-takes place in and through sequentially organized talk and action in psychotherapy. We conclude that the moment of meeting in our segment occurs not in parallel with the exchange of linguistic utterances between client and therapist. It occurs through the exchange of such linguistic utterances and through the sequence of actions carried out by that exchange. In this way, the sequential doing-together with words leads to a moment of meeting, bringing about change, at least momentarily, in the implicit ways-of-being-with-others of the client.